Capital requirements in Pillar 1 or Pillar 2: Does it matter for market discipline? - Niklas Witte (European Central Bank (ECB), 2024)
The results of this paper provide empirical evidence that regulatory capital ratios drive bank Credit Default Swaps (CDS) and that markets react more to changes in capital requirements if implemented via direct adjustments to Pillar 1 risk weights than imposed as a percentage of Risk-Weighted Assets (RWAs) under Pillar 2. In other words, market discipline on bank capital adequacy is sensitive to the composition of the capital requirement stack. Therefore, this paper contributes novel insights to existing research on the market relevance of regulatory capital ratios, on the functioning of the Basel framework, and on market discipline along with its relationship with Pillar 1 and Pillar 2 capital requirements. The findings are relevant in light of the continuous discussions around the capital regulation for Interest Rate Risk in the Banking Book (IRRBB) and other Pillar 2 risks because they suggest that risks are more disciplined by markets if they are reflected in regulatory capital ratios via RWAs. Moreover, the results suggest that further regulatory alignment within the EU can impact the comparability of regulatory capital ratios and affect pricing decisions. In the first empirical step, the research investigates the drivers of CDS and identifies a significant relationship between CDS spreads and regulatory capital ratios. In the second step, the paper researches a quasi-natural experiment based on an event in the EU banking sector. In 2018, the Swedish supervisory authority changed the implementation approach of a risk weight floor on Swedish mortgages by shifting it from Pillar 2 to Pillar 1 while keeping total capital requirements stable. To assess if this merely technical regulatory adjustment triggered an unexpected reaction by markets, a two-step system Generalised Method of Moments (GMM) regression is applied to a sample of CDS spreads of 21 European banks between 2014 and 2020.
Keywords: F36; G12; G21; G28; 330; European integration; banking regulation; capital requirements; bank default risk; funding costs; IRRBB; market discipline